Incidental findings in pancreas screening programs for high-risk individuals: Results from three European expert centers. Issue 5 (June 2019) - Ibrahim, Isaura S; Brückner, Catharina; Carrato, Alfredo; Earl, Julie; Inderson, Akin; de Vos tot Nederveen Cappel, Wouter H; Mintziras, Ioannis; Matthäi, Elvira; Figiel, Jens; Wasser, Martin; Moreau, Hans; Bonsing, Bert; et al.
Background: Widespread abdominal imaging has led to a substantial increase in the detection of incidentalomas. Currently, an increasing number of centers offer surveillance of the pancreas to individuals at high risk (IARs) of pancreatic ductal adenocarcinoma (PDAC). Objective: The aims of this study were to evaluate the frequency and type of incidental findings in a magnetic resonance imaging (MRI)-based surveillance program for IARs for PDAC, and to discuss the benefit of detecting these lesions. Methods: The outcome of MRI screening was reviewed in 568 individuals from three long-term pancreas surveillance programs conducted at three large European expert centers. All MRIs were studied in detail for the presence of incidental lesions. Results: The most common lesions were liver cysts, renal cysts and liver hemangioma, which together comprised 75% of all lesions. Only five (0.9%) patients underwent surgery for a benign lesion. Cancer was detected in 11 patients (1.9%); early detection of tumors was beneficial in at least five cases. Conclusion: The present study demonstrates that extrapancreatic incidentaloma is a common finding in IARs for PDAC, but rarely requires additional treatment. CDKN2A-p16-Leiden mutation carriers were the only patient group found to harbor a substantial number of cancers, and detection resulted in benefit in several cases.